Infrared thermography and capillaroscopy in the diagnosis of Raynaud's phenomenon - Sternbersky, Jan; Tichy, Martin; Zapletalova, Jana (Biomedical papers, 2021)
Aims. Raynaud's phenomenon (RP) is a relatively common disease. There are two distinct forms of RP - primary (PRP), where no other associated diseases are present, and secondary (SRP), where RP is associated with other diseases. It can be challenging to differentiate between RP and other diseases through medical history alone, due to the episodic nature of RP. Objective analysis of anamnestic data was performed in our study using infrared thermography (IRT) and a cold pressor test (CPT). Capillaroscopy was performed to assess morphological changes in the acral circulation. Methods. Patients with a history of cold hands were included in the study. IRT was performed before and after the CPT, and then capillaroscopy was performed. The results (including epidemiologic data) were statistically evaluated. Results. A total of 150 patients were included in the study. Summarisation of the results from the IRT and capillaroscopy determined the final diagnosis - 4.7% acrocyanosis, 10.7% physiologic findings, 31.3% PRP, 29.3% borderline SRP and 24% SRP. The coldest fingers following the CPT were, in most patients, the 2nd and 3rd fingers. The correlation between the presence of connective tissue disease and the diagnosis of borderline SRP and SRP was significant (P=0.0001). Conclusions. Using the combination of the IRT and capillaroscopy in the diagnostic algorithm for RP has its justification. IRT distinguishes healthy patients from patients with RP, and capillaroscopy can then be used to differentiate PRP from SRP. IRT can also detect which fingers are more affected, and then these can direct the focus of capillaroscopy.
Keywords: Raynaud's phenomenon; infrared thermography; cold pressor test; capillaroscopy; connective tissue disease